Crystallization, Microstructure, and Viscosity Evolutions in Lithium Aluminosilicate Glass-Ceramics - Fu, Qiang; Wheaton, Bryan R.; Geisinger, Karen L.; Credle, Allen J.; Wang, Jie (Frontiers in Materials, 2016)
Lithium aluminosilicate glass-ceramics have found widespread commercial success in areas such as consumer products, telescope mirrors, fireplace windows, etc. However, there is still much to learn regarding the fundamental mechanisms of crystallization, especially related to the evolution of viscosity as a function of the crystallization (ceramming) process. In this study, the impact of phase assemblage and microstructure on the viscosity was investigated using high temperature X-ray diffraction (HTXRD), beam bending viscometry (BBV), and transmission electron microscopy (TEM). Results from this study provide a first direct observation of viscosity evolution as a function of ceramming time and temperature. Sharp viscosity increases due to phase separation, nucleation and phase transformation are noticed through BBV measurement. A near-net shape ceramming can be achieved in TiO2-containing compositions by keeping the glass at a high viscosity (> 109 Pa.s) throughout the whole thermal treatment.